2017
DOI: 10.13189/bb.2017.050401
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Phytochemical Studies and Biological Potential of Citrullus colocynthis (L.) Schrad. (Cucurbitaceae)

Abstract: Cucurbits are edible crops found in the Cucurbitaceae family. Interest in plant-based biological compounds has now awakened throughout the world and hence the literature data in this area is significant. The Cucurbitaceae family is distributed in the tropical and subtropical countries. The plants of this family are superb fruit crops rich in vitamins, nutrients, and minerals that very good for health. A number of plants belonging to this family have been reported so far and one among them is Citrullus colocynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Each full MS scan was followed by data dependent MS/MS on the most intense ion using the collision-induced dissociation (CID) fragmentation mode at 35% normalized collision energy, with an isolation width of 2 Da and activation Q set at 0.250. The obtained spectra were compared with those from literature (Chawech et al, 2015;Dhakad et al, 2017;Gurudeeban et al, 2010;Hussain et al, 2014), in order to determine their identity, based on the molecular formula deduced from Tr, M+HCOO-and M+NH4+ values (see Table 1). The CAD profile was used to quantify the relative presence of the compounds in Pna1 (normalized to 100%).…”
Section: Extract Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…Each full MS scan was followed by data dependent MS/MS on the most intense ion using the collision-induced dissociation (CID) fragmentation mode at 35% normalized collision energy, with an isolation width of 2 Da and activation Q set at 0.250. The obtained spectra were compared with those from literature (Chawech et al, 2015;Dhakad et al, 2017;Gurudeeban et al, 2010;Hussain et al, 2014), in order to determine their identity, based on the molecular formula deduced from Tr, M+HCOO-and M+NH4+ values (see Table 1). The CAD profile was used to quantify the relative presence of the compounds in Pna1 (normalized to 100%).…”
Section: Extract Chromatographymentioning
confidence: 99%
“…At present, the plant (especially its fruit) is the topic of pharmacological investigations, mainly concerning its anti-diabetic and (cucurbitacin-related) anti-cancer effects (Hussain et al, 2014). Other current areas of investigation include those concerning its antihyperlipidemic (cholesterol-and triglyceride-lowering), anti-inflammatory, analgesic, insecticidal, and anti-microbial activities (Dhakad et al, 2017;Gurudeeban et al, 2010;Hussain et al, 2014). In addition to its medicinal value, the Citrullus colocynthis is also well-appreciated for its marked nutritional value, due to its high protein amount and the elevated concentration of essential amino acids (Gurudeeban et al, 2010;Hussain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical analysis of C. colocynthis and its parts exposed the presence of alkaloids, Flavonoids, Phenols, Saponins, and Diterpenes. The crude oil from seeds of C. colocynthis fruit showed that the major ingredients were mainly free fatty acids, triglycerides, phospholipids, and sterols, along with other minor unidentified constituents [6][7][8][9][10][11][12] .…”
Section: Phytochemical Constituents Of Citrullus Colocynthismentioning
confidence: 99%
“…The presence of phenolic compounds prompted us to evaluate their antioxidant activity. The fruit extract of C. colocynthis has been used for the treatment of elephantiasis, cancer, diabetes, inflammation, jaundice, leucoderma, microbial, edema, ulcer, and urinary diseases 8,11,12,31,29,[62][63][64][65][66][67][68][69][70][71][72][73][74] .…”
Section: Root and Stemmentioning
confidence: 99%
“…Phytochemical screening of the fruits of Citrullus colocynthis has revealed the presence of several bioactive compounds grouped as glycosides, flavonoids, alkaloids, phenols, carbohydrates, fatty acids, and essential oils 13 . Phenolic profile and antioxidant activity of various extracts from Citrullus colocynthis have been reported 14 .…”
Section: Cotylophoronmentioning
confidence: 99%